2013
DOI: 10.1073/pnas.1315295110
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 suppression and durable control by combining single broadly neutralizing antibodies and antiretroviral drugs in humanized mice

Abstract: Effective control of HIV-1 infection in humans is achieved using combinations of antiretroviral therapy (ART) drugs. In humanized mice (hu-mice), control of viremia can be achieved using either ART or by immunotherapy using combinations of broadly neutralizing antibodies (bNAbs). Here we show that treatment of HIV-1-infected hu-mice with a combination of three highly potent bNAbs not only resulted in complete viremic control but also led to a reduction in cell-associated HIV-1 DNA. Moreover, lowering the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
250
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(259 citation statements)
references
References 51 publications
3
250
1
1
Order By: Relevance
“…Recently, a human leukocyte reconstituted mouse model was developed to assess antibody mediated protection by neutralisation [43] and activating FcγR-dependent mechanisms [44]. The full potency of bNAbs in protection and control of viremia has been shown in this model to require FcγR-dependent extra-neutralising activity [44].…”
Section: In Vivo Studies I: Macaque and Mouse Modelsmentioning
confidence: 99%
“…Recently, a human leukocyte reconstituted mouse model was developed to assess antibody mediated protection by neutralisation [43] and activating FcγR-dependent mechanisms [44]. The full potency of bNAbs in protection and control of viremia has been shown in this model to require FcγR-dependent extra-neutralising activity [44].…”
Section: In Vivo Studies I: Macaque and Mouse Modelsmentioning
confidence: 99%
“…The human cells present in these animals have been shown to induce both innate and adaptive immune responses (46,53,(58)(59)(60)(61). In addition, HIV infection in these models responds to the same drugs used in humans (62)(63)(64)(65)(66)(67)(68). Like all animal models for biomedical research, there are limitations to their use in HIV research.…”
Section: Strengths and Limitations Of Current Humanized Mouse Modelsmentioning
confidence: 99%
“…Likewise, recent animal studies have shown that broadly neutralizing antibodies are indeed effective therapeutically. [78][79][80][81] In a human primate study, 3 out of 18 monkeys that exhibited the lowest viral loads prior to treatment exhibited prolonged virological control after the animals were treated with a PGT121-containing mAb cocktail and virus was cleared from the blood. However, while these mAbs cleared systemic virus transiently, the mAbs were unable to eradicate the reservoir in the majority of animals.…”
Section: Engineering Monoclonal Functionmentioning
confidence: 99%